2015
DOI: 10.1111/jphp.12417
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ruthenium on vascular tone

Abstract: Ruthenium-containing molecules can influence vascular tone induced by norepinephrine due to oxidative inactivation. Moreover, they can undermine NO-mediated responses. This should be considered when developing ruthenium-containing drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, these CORMs have shown to elicit effects independently of CO release . Recently, it was also found that ruthenium as such exerts some effects . Although in most cases these CO‐independent effects seem to be beneficial, possible undesired side effects should be kept in mind.…”
Section: Ruthenium‐based Co‐donating Moleculesmentioning
confidence: 99%
“…Furthermore, these CORMs have shown to elicit effects independently of CO release . Recently, it was also found that ruthenium as such exerts some effects . Although in most cases these CO‐independent effects seem to be beneficial, possible undesired side effects should be kept in mind.…”
Section: Ruthenium‐based Co‐donating Moleculesmentioning
confidence: 99%